2022
DOI: 10.1002/cam4.4574
|View full text |Cite
|
Sign up to set email alerts
|

DNA image cytometric analysis of bronchial washings as an adjunct for the detection of lung cancer in a clinical setting

Abstract: Background DNA aneuploidy has a potential to become an adjunct to conventional cytology for diagnosis of lung cancer, but its value in bronchial washings has not been well evaluated. Methods We conducted a retrospective study on patients who underwent bronchoscopy and the bronchial washings were submitted for both cytology and DNA image cytometry (DNA‐ICM) examination. The sensitivity and specificity of two methods and both in combination were compared. Analysis of clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The DNA histograms of corresponding patterns were are shown in Figure 1 , which was described in previous study. 19 Among the 30 patients with malignancy (Table 1 ), four patients (13.3%) were pathology positive and DNA‐ICM negative. Eight patients (26.6%) were DNA‐ICM positive while pathology negative.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DNA histograms of corresponding patterns were are shown in Figure 1 , which was described in previous study. 19 Among the 30 patients with malignancy (Table 1 ), four patients (13.3%) were pathology positive and DNA‐ICM negative. Eight patients (26.6%) were DNA‐ICM positive while pathology negative.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Patients who were lost to follow‐up without a clear diagnosis. (c) Patients with clinical manifestation of infection or with a large amount of purulent bronchial secretion under bronchoscope were excluded, as our previous study showed high false positive rate in such patients 19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the many signaling mechanisms of NO, it is appreciated that epigenetic regulation has gained ground in recent years. NO promotes an immunosuppressive microenvironment by modifying the redox state of cells, reprogramming cellular metabolism, and inducing changes in nucleic acids, lipids, and proteins [ 29 , 59 , 60 , 61 , 62 , 63 ]. All these effects of NO in melanoma are also supported by our results.…”
Section: Discussionmentioning
confidence: 99%